2009
DOI: 10.1007/s10151-009-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

Innovative technique for the closure of rectovaginal fistula using Surgisis™ mesh

Abstract: The preliminary success rate for this innovative technique using Surgisis mesh for the closure of rectovaginal fistulas is promising. Further studies are needed to assess the definite role of this novel technique in comparison to traditional surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…The shortest mean or median follow-up in the 20 studies was 3 months, and the longest follow-up was 24.5 months ( [60][61][62] Unable to separate rectovaginal, anovaginal or pouch-vaginal fistulas = 3 [63][64][65][66][67][68][69][70][71] Inadequate f/up = 1 59 Patients included in later publication = 19 [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Review articles, comments, conference proceedings = 12 1 Eight of the 20 included articles reported continence levels pre-and postinsertion of the AFP. 25,79,80,84,85,89,92,94 There were no reported cases of any significant change in continence after insertion of the AFP in any of the patients in these studies (n ϭ 196 patients).…”
Section: Resultsmentioning
confidence: 99%
“…The shortest mean or median follow-up in the 20 studies was 3 months, and the longest follow-up was 24.5 months ( [60][61][62] Unable to separate rectovaginal, anovaginal or pouch-vaginal fistulas = 3 [63][64][65][66][67][68][69][70][71] Inadequate f/up = 1 59 Patients included in later publication = 19 [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Review articles, comments, conference proceedings = 12 1 Eight of the 20 included articles reported continence levels pre-and postinsertion of the AFP. 25,79,80,84,85,89,92,94 There were no reported cases of any significant change in continence after insertion of the AFP in any of the patients in these studies (n ϭ 196 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Schwandner et al [41] reported using Surgisis™ mesh in 21 patients with RVF, 9 with Crohn's RVF. After a mean follow up of 12 mo, they achieved a 78% closure rate in the Crohn's group and an 83% closure rate in the non-Crohn's RVF.…”
Section: Miscellaneous Repairsmentioning
confidence: 99%
“…After a mean follow up of 12 mo, they achieved a 78% closure rate in the Crohn's group and an 83% closure rate in the non-Crohn's RVF. The authors concluded that the mesh plug could be used as an adjunct to traditional advancement flap repair or muscle interposition, or possibly it could be used as an initial operation [41] . In a study by O'Connor et al [42] , the use of the fistula plug was studied in patients with Crohn's fistulae (2 with RVF) with an 80% success rate.…”
mentioning
confidence: 99%
“…Several authors reported that a successful outcome can be achieved without the use of a stoma [7,13,21]. However, it is often stated that in difficult cases faecal diversion should be considered.…”
Section: Discussionmentioning
confidence: 97%